Oxidative Stress and Gut Microbiome in Inflammatory Skin Diseases - Ni, Qingrong; Zhang, Ping; Li, Qiang; Han, Zheyi (Frontiers in Cell and Developmental Biology, 2022)
Oxidative stress plays a dominant role in inflammatory skin diseases. Emerging evidence has shown that the close interaction occurred between oxidative stress and the gut microbiome. Overall, in this review, we have summarized the impact of oxidative stress and gut microbiome during the progression and treatment for inflammatory skin diseases, the interactions between gut dysbiosis and redox imbalance, and discussed the potential possible role of oxidative stress in the gut-skin axis. In addition, we have also elucidated the promising gut microbiome/redox-targeted therapeutic strategies for inflammatory skin diseases.